Analisis Pengaruh Kepuasan Pelanggan, Citra Perusahaan dan Kepercayaan pada Loyalitas Pelanggan Taksi Express di Jakarta - , Hotma Rina Janita Sitorus; , Prof. Dr. Basu Swastha Dharmmesta, M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Today, the growth of a taxi services is significantly increasing in major cities, especially in Jakarta, which is characterized by increased number of taxis and companies engaged in taxi service. The number of taxi companies operating in Jakarta varies inversely with the least choice of brands which may be chosen by taxi customers due to low image or reputation of taxi brands mostly. One of the key to success and also one of essential elements of the company to compete with similar companies are customer loyalty. However, effort to mantain customers which is important part in building customer loyalty is not simple due to the strict competition, as is happening in the taxi companies in Jakarta. In the case of Express taxi, the customers tend to decrease in line with the increase of numbers of taxi companies and units of taxi in Jakarta. This condition is influenced by three factors: customer satisfaction, corporate image and customer trust. This study aims to determine the effect of customer satisfaction, corporate image and customer trust on customer loyalty, with the object of research is customers of Express taxi in Jakarta. Data is collected through the questionnaire survey method (with the number of respondents are 170 respondents), and testing of research instruments by test of validity and reliability, and factor analysis using the CFA approach (confirmatory Factor Analysis) is calculated using SPSS afterwards. Furthermore, the results of test are then analyzed using descriptive and inferential, which means each of data result tabulation aimes to determine the condition of each variable, according to the responses of study and to test the research hypotheses and also to know which variables are most influential of the three dependent variables against the independent variables (customer loyalty). The final results of this study hopefully will be able to increase the loyalty of Express customer.